2022
DOI: 10.1101/2022.04.11.487940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the interaction between Janzen-Connell effects and habitat partitioning in spatially structured environments

Abstract: Janzen-Connell Effects and Habitat Partitioning have both been proposed as potential stabilizing mechanisms in species-rich forest communities. Janzen-Connell Effects describe the process in which specialized predators are attracted to adult trees, which reduce the survivorship of nearby conspecific juveniles. This is thought to generate stabilizing negative frequency dependence. Habitation Partitioning describes when species exhibit different fitness responses to spatially heterogeneous environmental factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…We also treat space implicitly in our model, but the spatial structure of ecological landscapes could shape how patch modification and dispersal interact. For example, a recent theoretical analysis incorporating both habitat partitioning and Janzen-Connell effects (endogenous heterogeneity) showed that these processes can combine to promote coexistence in a strongly synergistic manner when the spatial autocorrelation of patches is accounted for (Smith 2022). Even when only one source of heterogeneity is present, the spatial arrangement of patches could modulate our understanding of coexistence, for instance by reducing source-sink effects that limit the coexistence of imperfect habitat specialists (Snyder & Chesson 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also treat space implicitly in our model, but the spatial structure of ecological landscapes could shape how patch modification and dispersal interact. For example, a recent theoretical analysis incorporating both habitat partitioning and Janzen-Connell effects (endogenous heterogeneity) showed that these processes can combine to promote coexistence in a strongly synergistic manner when the spatial autocorrelation of patches is accounted for (Smith 2022). Even when only one source of heterogeneity is present, the spatial arrangement of patches could modulate our understanding of coexistence, for instance by reducing source-sink effects that limit the coexistence of imperfect habitat specialists (Snyder & Chesson 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many studies – and even sub-fields of ecology – focus on a single source of heterogeneity, making it hard to draw general conclusions that cut across system specifics. In particular, fixed or “exogenous” heterogeneity and biotically-generated or “endogenous” heterogeneity have often been approached from very different perspectives (Bolker 2003; Smith 2022). Our models and analysis help overcome these challenges by providing coexistence criteria that extend naturally to communities of arbitrary size, and by building endogenous environmental feedbacks directly into a core model for landscapes with exogenous heterogeneity.…”
Section: Introductionmentioning
confidence: 99%